Non-Coding RNAs in CD4+ T Cells: New Insights Into the Pathogenesis of Systemic Lupus Erythematosus - Gao, Xiaofei; Liu, Limin; Min, Xiaoli; Jia, Sujie; Zhao, Ming (Frontiers in Immunology, 2020)
Noncoding RNAs (ncRNAs) are indispensable for CD4+ T cell differentiation and functions. By directly or indirectly regulating immune gene expression, ncRNAs give flexible instructions to guide the biological processes of CD4+ T cells and play a vital role in maintaining immune homeostasis. However, the dysfunction of ncRNAs alters the gene expression profiles, disturbs the normal biological processes of CD4+ T cells, and leads to the functional changes of CD4+ T cells, which is an underlying cause of systemic lupus erythematosus (SLE). In this review, we focus on the recent advances in the roles of ncRNAs in CD4+ T cell functions and differentiation, as well as their potential applications in the diagnosis and treatment of SLE.